Algenpantucel-L immunotherapy in pancreatic adenocarcinoma. (February 2016) - Coveler, Andrew L; Rossi, Gabriela R; Vahanian, Nicholas N; Link, Charles; Chiorean, E Gabriela
Pancreatic adenocarcinoma is the 4th leading cause of cancer death in the USA and the EU. A minority of patients presents with surgically resectable and potentially curable disease, but among these, 80% are destined to relapse and overall survival rates with adjuvant chemotherapy average 24 months. Immunotherapy is a promising therapeutic option and a potential paradigm shift in the treatment of patients with pancreatic cancer, and may be particularly effective when used early in the disease course to prevent metastatic spread. Algenpantucel-L (HyperAcute™ Pancreas, NewLink Genetics, Ames, IA, USA) is a whole-cell immunotherapy consisting of irradiated allogeneic pancreatic cancer cells genetically engineered to express the murine enzyme α-GT, which results in hyperacute rejection of the tumor cells with complement- and antibody-dependent cytotoxicity. Phase II clinical trial data has been encouraging, particularly for patients who demonstrated humoral immunologic responses. Here, we report preliminary results and biomarkers correlations with clinical activity of algenpantucel-L in pancreatic cancer.